The Relationship Between Task Aversiveness and Academic Procrastination Among Psychology Students at UIN Ar-Raniry Banda Aceh - Putri, Ferlita; Safrilsyah, Safrilsyah; Hidayati, Siti Hajar Sri; Andriyani, Juli (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Task aversiveness has an impact on students’ tendency to engage in academic procrastination. This study aims to determine the relationship between task aversiveness and academic procrastination among Psychology students at UIN Ar-Raniry Banda Aceh. The research employed a quantitative approach using a correlational method. The instruments used in this study were the Task Aversiveness Scale and the Academic Procrastination Scale. The sample consisted of 221 Psychology students at UIN Ar-Raniry Banda Aceh. Sampling was conducted using the probability sampling method with the stratified random sampling technique. Data were analyzed using the Spearman’s rho correlation test. The results showed a correlation coefficient (rho) of 0.492 with a significance value (p) = 0.000, indicating a significant positive relationship between task aversiveness and academic procrastination among Psychology students at UIN Ar-Raniry Banda Aceh. This means that the higher the level of task aversiveness, the higher the academic procrastination, and conversely, the lower the task aversiveness, the lower the academic procrastination.